(untitled) (Journal of Parents and Teachers, 2012)
In this article, the author introduces the film ’Kathmandu. A mirror in the sky’ as a guide of pedagogical intervention. This guide consists on a summary and a specification sheet; a section of topics and values to discuss; activities to watch before the movie; some rules about the development of the cinema-forum; curiosities of interest about the movie and some educational proposals to answer after watching the movie; proposals that are for action and reflection-action. With all this teaching materials, we try to know, understand and value the cinematographic language and its didactic possibilities to educate in values our students not only on formal fields but also on informal ones.